2011
DOI: 10.1257/app.3.1.101
|View full text |Cite
|
Sign up to set email alerts
|

The Labor Market Returns to Cognitive and Noncognitive Ability: Evidence from the Swedish Enlistment

Abstract: We use data from the military enlistment for a large representative sample of Swedish men to assess the importance of cognitive and noncognitive ability for labor market outcomes. The measure of noncognitive ability is based on a personal interview conducted by a psychologist. Unlike survey-based measures of noncognitive ability, this measure is a substantially stronger predictor of labor market outcomes than cognitive ability. In particular, we …nd strong evidence that men who fare badly in the labor market -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
185
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(210 citation statements)
references
References 56 publications
19
185
1
5
Order By: Relevance
“…We also show that the data, in general, are less in line with the model when studying recruitments to jobs with a lower skill content. The patterns also suggest that non-cognitive abilities are more relevant for jobs with a low skill content which is well in line with the notion that cognitive skills primarily are linked to productivity within high skilled jobs, and that non-cognitive skills are relatively more important within less skill demanding jobs (see also Lindqvist andVestman (2011) andBrown et al (2012) for similar conclusions).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…We also show that the data, in general, are less in line with the model when studying recruitments to jobs with a lower skill content. The patterns also suggest that non-cognitive abilities are more relevant for jobs with a low skill content which is well in line with the notion that cognitive skills primarily are linked to productivity within high skilled jobs, and that non-cognitive skills are relatively more important within less skill demanding jobs (see also Lindqvist andVestman (2011) andBrown et al (2012) for similar conclusions).…”
supporting
confidence: 76%
“…As when Burks et al (2013) analyze call centers and truckers, links do not result in entrants with better cognitive or non-cognitive skills in our broad sample of low skilled jobs, although network inbreeding is still present. The results further suggest a notable heterogeneity in the importance of different types of skills along the IFAU -Social networks, employee selection and labor market outcomes 39 lines suggested by Lindqvist and Vestman (2011). In particular, while cognitive skills are a better predictor of linked hires in high-skilled jobs, it is the non-cognitive skills of the incumbent worker that predict the recruitments of linked entrants into low skilled jobs.…”
Section: Extending the Analysis To Low-skilled Jobsmentioning
confidence: 70%
See 1 more Smart Citation
“…For our empirical analysis, we proceed similarly as for cognitive ability and standardize the non-cognitive ability variable by birth year using all individuals with non-missing data on this variable. Lindqvist and Vestman (2011) have previously shown that both our cognitive and non-cognitive measures strongly predict adult earnings in the population of Swedish males.…”
Section: A Data Descriptionmentioning
confidence: 83%
“…8 See, for example, Ng et al (2001), Ettner et al (1997), Ettner et al (2011), Famulari (1992, Ferrari (1998), Krahn et al (1996), Malone et al (1997), Fanning (1981, and Currie et al (2010). particular this implies an assessment of personal characteristics such as willingness to assume responsibility, independence, outgoing character, persistence, emotional stability and power of initiative (Lindqvist and Vestman 2011). In addition, an important objective of the interview is to identify individuals who are considered particularly unsuited for military service, which includes individuals with antisocial personality disorders, individuals with difficulty accepting authority, individuals with difficulties adjusting to new environments and individuals with violent and aggressive behavior (Andersson and Carlstedt, 2003;Lindqvist and Vestman 2011).…”
Section: A Data Descriptionmentioning
confidence: 99%